'I'm not prepared to sacrifice my life for other people's tennis': An explorative study into the career narratives of female tennis coaches. Issue 2 (April 2023) - Jones, Ellen; Edwards, Lisa; Dohme, Lea-Cathrin; Norman, Leanne
Research recognises the existence of a dominant performance narrative in elite sport that values a 'win at all costs' attitude, prioritising sport over all other facets of life. This narrative commonly privileges dominant groups of men at the expense of marginalised men and many women. To interrogate this aspect of sporting culture further, this study offers a unique insight into the influence of the dominant performance narrative within the coaching context. Specifically, a narrative analysis approach was employed to explore eight female tennis coaches' career experiences. Findings suggest that career success was judged on adherence to the dominant performance narrative which required a single-minded dedication to coaching. Whilst some of the coaches aligned closely with this narrative, adherence to the exclusive nature of the performance narrative caused tension and conflict for others. The coaches who did not adhere to the dominant performance narrative resisted cultural norms and aligned themselves with other, less dominant narratives. This highlights that career success in coaching can be a multidimensional concept and importantly that organisational culture needs to change in order that alternative narratives become more available and validated. This could lead to coach identity being less tied to adherence to the dominant performance narrative and focused more on personal development and well-being. Ultimately, this may result in higher levels of female coach attraction, retention, and progression.